The Impact of Oil and Gas Extractive Activity on Artisanal Fishing - Villalobos Porras, Eduardo Martin (2022)
This article reviews the extractive industry of offshore oil and gas, as well as its impact on affected populations on the north coast of Peru. It shows how these industries emphasize some issues related to environmental regulations, development of oil company operations, corporate strategies in managing the negative and positive impacts that productive activities may cause in the people’s and civil society’s expectations related to artisanal fishing activity. Following this review, some ideas are proposed for discussion or as contributions. Linked to the concept of sustainable development, they will allow us to rethink how these economic activities interact, incorporating the concept of circular economy and, if possible, peaceful coexistence between offshore oil industry extractive activities and activities exploiting sea resources.